O impacto do Programa Agente Rural sobre nível tecnológico, geração de emprego, renda e qualidade de vida das famílias assistidas do Estado do Ceará - Ferreira, Verônica Sousa (2009)
The aim of this study is to evaluate the Rural Agent Program (RAP) impact about the performance of assisted producers in the selected city. For this purpose, was realized a survey of primary datas in the Baturité, Iguatu and Quixadá cities. Ninety questionnaries were applied, 45 for assisted producers and 45 for non assisted producers, randomly selected. Tabular analysis, t-Student and Hof Kruskall-Wallis tests were realized for comparison of the average and ratio, respectively with the finality to measure the program impact about the assisted producers in Ceará State. The research observed that, in general, the assisted producers have socioeconomic characteristics more favorable in utilization of new technologies, sch as age, instruction degree and ownership of the land in relation to the non-assisted. Thus, was concluded that socioeconomic characteristics of assisted producers contributed with theirs technology levels and consequently with employment and income generation. Comparing the producers groups is verified that the assisted producers through RAP it presented great technology level in relation to non assited producers. The RAP it presents positive impacts in employment and income generation of assisted producers. In general, the quality of life index of assisted producers is superior in relation to non-assisted. The evaluation of producers in relation to the quality service done by rural agents is satisfactory. This show that in despite of the number of agents in the cities to be still little to attend the existent demand, the program has been beneficed the assisted families.